Hysteroscopic assessment of patients with abnormal uterine bleeding: a prospective study at a tertiary care hospital - Nachiketha, S.V. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Hysteroscopy has been found useful to evaluate the problem of abnormal uterine bleeding. It helps to resolve this by direct view of uterus. It is useful in detecting endometrial hyperplasia. Objective of the study is to evaluate the role of Hysteroscopy in the diagnosis of patients with AUB and Correlate HPR findings. Methods: Total 50 woman who presented with complaints of abnormal uterine bleeding were studied for one year from December 2012 to November 2013. The observations obtained were analyzed. Results: Total of 50 women presenting with complaints of abnormal uterine bleeding were enrolled. Data obtained analyzed and final results and observations were tabulated pertaining to age, Chief complaints, Duration of symptoms, Menopause, Parity, Hysteroscopic/HPR findings, Accuracy obtained correlating with HPR. Conclusions: Hysteroscopy is highly sensitive diagnostic procedure which not only provides useful information of the uterine cavity but also an ideal method for the evaluation of patients with abnormal uterine bleeding.